2018
DOI: 10.1021/acscatal.8b02935
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme–Polyelectrolyte Complexes Boost the Catalytic Performance of Enzymes

Abstract: Understanding interactions between polymers and enzymes to boost enzymatic activity is of high importance for application of enzymes in multicomponent systems, such as laundry, food, pharmaceuticals, or cosmetics. Proteases are widely used in industries and increased performance in the presence of polymers has been reported. Boosting of enzymes activity by polymers and understanding of the molecular principles is of high interest in biomedical and biotechnological applications. A molecular understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…First, the interaction of the enzyme with the polymer in the liquid droplets may increase the structural stability of the native enzyme, leading to an increased kcat. [21][22][23] Second, liquid droplets are highly crowded with macromolecules, resulting in the exclusion of water molecules. This crowding stabilizes nonnative structures that differ from those in dilute conditions.…”
Section: Discussionmentioning
confidence: 99%
“…First, the interaction of the enzyme with the polymer in the liquid droplets may increase the structural stability of the native enzyme, leading to an increased kcat. [21][22][23] Second, liquid droplets are highly crowded with macromolecules, resulting in the exclusion of water molecules. This crowding stabilizes nonnative structures that differ from those in dilute conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A bottlebrush polymer tightly linked on a solid core of PS was also investigated as an Ag nanoparticle carrier platform. However, the synthesis method is complicated, which can lead to high costs and difficulties in raw materials personnel, and time, restricting broad realistic implementations [113,114].…”
Section: Photodegradation Of Mb~99%mentioning
confidence: 99%
“…We suppose prolonging the spacer arm between the p NBC moiety and the main chain can weaken the steric effect and hence make the substrate more accessible to the active site of NTR. Furthermore, it is reported that the enzyme activity can be modulated by the noncovalent interactions between the enzyme and polymer 27–29 . The interactions can be induced by van der Waals forces, electrostatic interactions, hydrophobic interactions, and hydrogen bonding 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is reported that the enzyme activity can be modulated by the noncovalent interactions between the enzyme and polymer. [27][28][29] The interactions can be induced by van der Waals forces, electrostatic interactions, hydrophobic interactions, and hydrogen bonding. 30 For example, the complementary electrostatic interactions between a polymer and a protein have been utilized to bring about a binding-induced substrate selectivity to the enzyme.…”
Section: Introductionmentioning
confidence: 99%